ANTIARRHYTMIC EFFICACY OF SOTALOL IN PATIENTS WITH TACHY-BRADY SYNDROME HAVING ATRIAL PACEMAKER WITH DIFFERENT ATRIAL ELECTRODE POSITION - T. N. Novikova (Столичная издательская компания, 2016)
Aim. To evaluate efficacy of the combined therapy (sotalol and constant electric cardiostimulation in AAI regimen) at two atrial electrode position: in low back part of interatrial septum (IAS) and in right atrial auricle (RAA).Material and methods. 20 patients with tachy-brady syndrome were examined. They were randomized in 2 groups depending on atrial electrode position. Sotalol (160 mg daily) was prescribed to all patients in a month after implantation of constant atrial pacemaker (CAP). A number of atrial fibrillation paroxysms (AFP) was evaluated initially, in a month after CAP implantation and in a month after start of sotalol therapy.Results. Significant AFP reduction was observed in IAS stimulation, unlike RAA stimulation. Sotalol addition had essential significance in the termination or reduction of AFP. Sotalol effect did not depend on atrial electrode position.Conclusion. Sotalol usage together with constant electric cardiostimulation significantly reduces AFP irrespectively of atrial electrode position.